Analysis for metal sheath corrosion rate in AC high voltage power cable - Lai, Lin‐Hua; Wu, Zhi‐Heng; Liu, Xiao‐Dong; Hao, Yanpeng; Liu, Gang (IET generation, transmission & distribution, 2022)
Reliable power transmission requires the safe operation of high‐voltage cable. A number of high‐voltage cable failures caused by aluminium sheath corrosion has been reported these years. However, neither discussion on factors influencing corrosion rate nor specification describing corrosion inhibiting method has been presented. Thus, it is crucial to address the research gap in evaluating corrosion rate of aluminium sheath in various corrosive environments. Here, the effect of chlorides on aluminium sheath corrosion is analyzed. Using scanning electron microscopy (SEM) and energy dispersive spectrometer (EDS), the corroded surface is investigated. Titration experiment is performed to quantify the chlorides content in buffer layer of cable. Polarization curves are employed to analyze the corrosion rate of aluminium sheath in different chlorides content environment. Surface analysis result shows that chlorine‐rich phase can be observed on the corroded surface. Titration experiment result reveals that buffer layer used in high voltage cable is one of the sources of chlorides content which varies from 0.7 to 4.2 wt%. Finally, polarization curve shows that when chloride content increases from 0.6 to 1.8 wt%, the pitting potential left shifts from −0.689 to −0.742 V. The corrosion resistance of aluminium sheath deteriorates significantly with the increase of chlorides content.